2004
DOI: 10.1016/j.colsurfa.2004.07.026
|View full text |Cite
|
Sign up to set email alerts
|

DNA and surfactants in bulk and at interfaces

Abstract: Recent investigations of the DNA interactions with cationic surfactants and catanionic mixtures are reviewed. Several techniques have been used such as fluorescence microscopy, dynamic light scattering, electron microscopy, and Monte Carlo simulations.The conformational behaviour of large DNA molecules in the presence of cationic surfactant was followed by fluorescence microscopy and also by dynamic light scattering. These techniques were in good agreement and it was possible to observe a discrete transition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 85 publications
(125 reference statements)
6
70
0
1
Order By: Relevance
“…The presence of surfactants may change the behavior of a polymer in solution. This can be exemplified by surfactant-induced thickening (Antunes, Marques, Miguel, & Lindman, 2009;Barreiro-Iglesias, AlvarezLorenzo, & Concheiro, 2003b;Cabane & Duplessix, 1982;Franç ois, Dayantis, & Sabbadin, 1985;Goddard & Ananthapadmanabhan, 1993;Holmberg, Jönsson, Kronberg, & Lindman, 2003;Lange, 1971;Lee, 1999), surfactant-induced swelling (Barreiro-Iglesias et al, 2003b) or compaction (Dias et al, 2004), surfactant-induced phase separation (Goddard & Ananthapadmanabhan, 1993;Holmberg et al, 2003), among other effects.…”
Section: Introductionmentioning
confidence: 96%
“…The presence of surfactants may change the behavior of a polymer in solution. This can be exemplified by surfactant-induced thickening (Antunes, Marques, Miguel, & Lindman, 2009;Barreiro-Iglesias, AlvarezLorenzo, & Concheiro, 2003b;Cabane & Duplessix, 1982;Franç ois, Dayantis, & Sabbadin, 1985;Goddard & Ananthapadmanabhan, 1993;Holmberg, Jönsson, Kronberg, & Lindman, 2003;Lange, 1971;Lee, 1999), surfactant-induced swelling (Barreiro-Iglesias et al, 2003b) or compaction (Dias et al, 2004), surfactant-induced phase separation (Goddard & Ananthapadmanabhan, 1993;Holmberg et al, 2003), among other effects.…”
Section: Introductionmentioning
confidence: 96%
“…An important addition to this list is fluorescence microscopy (FM), which was used to observe the condensation of single large T4 DNA molecules [5,6,17]. It has been used in a large number of studies on the interaction between DNA and different compacting agents [4,9,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, DNA molecules exist in a highly packed state in living cells. It has been found that isolated DNA chains undergo a coilglobule transition upon the increasing concentration of condensing agents in solution [5][6][7]. Chemical agents cause compaction by modifying electrostatic interactions between DNA segments, by modifying DNA-solvent interactions, by excluding volume to the worm-like coil (and/or counterions), by causing localized bending or distorsion of the helical structure, or by some combination of these effects.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by the results of surfactant ion-selective electrode measurements, the binding of DNA to hexadecyltrimethylammonium bromide followed two-stage firstorder kinetics for denatured (single-stranded) DNA and three-stage first-order kinetics for native DNA (Maulik et al 1998). The collapsing effect from extended DNA coils to compacted globules upon the addition of single chain cationic surfactant was observed by fluorescence microscopy and dynamic light scattering techniques (Dias et al 2004). From the small-angle X-ray scattering measurements it follows that DNA/single chain cationic surfactants complexes form hexagonal structures for longer chain surfactants (dodecyl-, tetradecyl-and hexadecyltrimethylammonium bromides) (Miguel et al 2003).…”
Section: Dna/conventional Cationic Surfactant Complexmentioning
confidence: 99%